Contribution of rattan cane in livelihood resilience in relation to Community Forest User Groups and Rattan Processing Enterprises in Nepal - Chowdhary, Chhote Lal; Dutta, I.C. (Nepal Journal of Multidisciplinary Research, 2021)
This study highlights the contribution of rattan cane in livelihood resilient of rural people in Nepal. Rattan cane is used as raw material for rattan processing enterprises as well as livelihood resilient of community people. The study was designed based on the exploratory research and was carried out in Community Forest User Groups (CFUGs) Kailali and Bardia district including rattan processing enterprises of major cities in Nepal. The main objective was to assess the contribution of rattan on capitals of Sustainable Livelihood Approaches (SLA) that increase resilient of community people. Systematic random sampling method was followed to take the sampling of rattan processing enterprises and CFUGs. Primary data was collected through open-ended questionnaire, and direct observations; and secondary data was collected from business reports, Forest Operational Plans, and audit reports. The questionnaire survey was conducted to 35 rattan entrepreneurs and rattan traders, and ten executive committee members of CFUGs and 526 household members. The quantitative data was analyzed using frequency of SPSS 20 software tools. The study found that rattan has been important source of income to improve their human capital, natural capital, physical capital, social capital and financial capital in relation to livelihood resilient in the community level, and creation of job in the enterprise level. The major constraints concerning the livelihood resilient was that investment was focused community development rather than household income, investment on rattan development and management was low, and weak employability focus. The study also identified a number of opportunities in the livelihood perspective such as enterprise development, employment generation to youths and linkage with service providers.